Freedom of contract versus standard contract: Pros or cons of the principle of balance in contracts in the study of the civil code and compilation of sharia economic law - Zaini Munawir S; Muhammad Yadi Harahap (Priviet Social Sciences Journal, 2025)
Freedom of contract is a core principle of contract law that empowers the parties to define the substance, structure, and conditions of their agreement, provided that it does not contravene statutory regulations, moral standards, or public order. However, the development of modern business practices shows the dominant use of standard contracts that are drawn up unilaterally, potentially shifting the bargaining position of the parties and creating an imbalance in the contractual relationship. This study aims to analyze the pros and cons of applying the principle of freedom of contract in standard contracts and examine the relevance of the principle of balance from the perspective of the Civil Code (KUH Perdata) and the Compilation of Sharia Economic Law (KHES). The research method used is normative legal research with a statutory and conceptual approach. The results of the study indicate that the Civil Code tends to place freedom of contract as the main principle, although it still leaves room for limitations through the principles of good faith and fairness. Meanwhile, KHES explicitly emphasizes the principles of balance, justice, and benefit as the main foundation of contracting, thereby providing stronger protection for the weaker party in standard contracts. Thus, it can be concluded that the implementation of standard contracts requires strengthening the principle of balance so that the freedom of contract does not turn into a means of unilateral domination, both within the framework of positive civil law and sharia economic law.